2023
DOI: 10.1037/ser0000679
|View full text |Cite
|
Sign up to set email alerts
|

Does prior law enforcement experience affect scores on preemployment psychological testing? An investigation using the MMPI-3.

Abstract: Most states require that a police candidate's suitability be assessed through preemployment psychological evaluations. Given the psychological stress officers experience in the line of duty, it is possible that experienced candidates would produce scores indicating greater dysfunction on psychological testing relative to inexperienced candidates. No known research has investigated whether police candidates produce different preemployment test scores across experience levels. The present study sought to address… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 48 publications
(97 reference statements)
1
5
0
Order By: Relevance
“…All data came from an archival dataset, a subset of which was previously analyzed (Menton et al, 2022; Sellbom et al, 2021; Whitman, Corey & Ben-Porath, 2022), and subsets of which is included in the MMPI-3 Police Officer, Correction Officer, Dispatcher, and Firefighter Comparison Groups. Public safety candidates were referred by 154 hiring agencies to the second author’s private practice for psychological evaluations following the conditional offer of employment.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…All data came from an archival dataset, a subset of which was previously analyzed (Menton et al, 2022; Sellbom et al, 2021; Whitman, Corey & Ben-Porath, 2022), and subsets of which is included in the MMPI-3 Police Officer, Correction Officer, Dispatcher, and Firefighter Comparison Groups. Public safety candidates were referred by 154 hiring agencies to the second author’s private practice for psychological evaluations following the conditional offer of employment.…”
Section: Methodsmentioning
confidence: 99%
“…To date, two peer-reviewed studies investigated the validity and clinical utility of MMPI-3 scores in police and other public safety candidates (Whitman et al, 2021; Whitman, Corey & Ben-Porath, 2022). The first, Whitman et al (2021), evaluated the validity of inferences drawn from MMPI-3 scores, but also the generalizability of these inferences across male and female police candidates and across police candidates and an aggregate sample of nonpolice public safety candidates.…”
Section: Mmpi-3 Scores In Preemployment Contextsmentioning
confidence: 99%
See 2 more Smart Citations
“…Whitman et al (2021) also found minimal differences in validity coefficients across male and female police candidates and across police and other public safety candidates. In another validation study, Whitman et al (2023b) demonstrated that police candidates produced similar MMPI-3 scores regardless of level of prior police officer experience. In a third study, Whitman et al (2023a) provided empirical support for the validity of MMPI-3 scores by reporting correlations with psychosocial history findings collected from police officer, correctional officer, dispatcher, and firefighter candidates.…”
mentioning
confidence: 97%